An analysis of microbiological parameters of septage as related to septic tank management and design Cagayan de Oro City, 1998-1999 - Beja, Rachel Mejias (2000)
In an attempt to characterize the septage of Cagayan de Oro City, the parameters like coliforms and ascaris eggs were determined from septic tank sludge and effluents. The results were related to septic tank design and management parctices such as vault capacity, number of tank users and desludging frequency (sludge retention time). Samples were taken from 25 septic tanks, five from each of the five barangays considered.